A Nurse-Led Mobility Program on an Acute Rehabilitation Unit. Issue 3 (July 2018) - Anton, Paula; Richard, Christy
Abstract : Rehabilitation assists patients with return to baseline activities of daily living after catastrophic events or long hospitalizations. In an effort to increase mobility episodes in the rehabilitation patient, a nurse-led mobility program was suggested. This allows the rehabilitation nurse to participate in the improvement of mobility for rehabilitation patients by mobilizing the patients safely during hours in which physical therapy is not available. The purpose of this project was twofold: (1) Can additional mobility episodes improve outcomes in the rehabilitation patient? (2) How can safe patient handling principles be applied to the rehabilitation patient?